Manufacturing Plants: Notes on the Culture of Nature and the Nature of Culture - Busch, Lawrence (The International Journal of Sociology of Agriculture and Food, 1991)
The terms "culture" and "nature" have ambiguous meanings in most Western societies. Culture is used to denote the totality of socially transmitted customs and behavior patterns of a given society as well as to denote the cultivation of plants or microorganisms in a petri dish. Nature is used to refer to those aspects of the world that are beyond us as well as to that which is taken for granted as "natural" or normal. This ambiguity is particularly well reflected in current debates about plant biotechnology and germplasm conservation.The thesis of this paper is that the nature/culture distinction has outlived its usefulness. The new biotechnologies illustrate in the most dramatic of ways how we make and remake nature, while the issues surrounding germplasm conservation show that we have been collectively engaged in making nature for thousands of years. Thus, nature is not natural; it is a product of culture. Put another way, nature is always cultured. Similarly, culture is a product of nature; it is natural in its origins if not in its content. ResumenIndustrializando el Cultivo: Notas sobre la Cultura de la Naturaleza y la Naturaleza de la Cultura Los términos "cultura" y "naturaleza" tienen significados ambiguos en la mayoría de las sociedades occidentales. El de Cultura es utilizado para denotar el conjunto de costumbres y patrones de comportamiento que tienen las sociedades. Asimismo también significa el cultivo de plantas o de microorganismos en una cápsula de Pietri. El de Naturaleza es utilizado para designar aquellos aspectos del mundo que nos rodean, así como también, para dar por sentado lo que es normal o "natural". Esta ambiguedad está particularmente bien reflejada en los actuales debates sobre la siembra biotecnológica y la conservación de plasma germinal. La tesis de este artículo es que la utilidad de la distinción naturaleza cultura ho terminado. Las nuevas biotecnologías ilustran, a través de las más dramáticas vías, cómo nos apropiamos y rehacemos la naturaleza, mientras miramos los beneficios de la conservación del plasma germinal comprometiendo colectivamente lo que la naturaleza ha hecho en miles de años. De este modo, la naturaleza ya no es natural; ella es un producto de la cultura. Por otro lado, la naluraleza es también culturizada. Similarmente, la cullura es un producto de la naturaleza; ella es naturaleza en sus origen pero no en su contenido.